Theories, methods, and practical needs of human-water relationship research - ZUO Qiting (Ziyuan Kexue)
Human-water relationship is one of the most fundamental relationships between humans and nature. Research on the human-water relationship is a crucial foundation for scientifically understanding water issues and exploring solutions to water management, as well as a practical necessity for the development of human society. Building on previous research and synthesizing results from various periods, this study provided a comprehensive review of the development of human-water relationship research in three stages: emergence, initiation, and formation, and summarized the developmental characteristics of each stage. A classification scheme for human-water relationships was proposed from three perspectives: system, subsystem, and research perspective. This study elaborated on the purpose and advantages of developing the human-water relationship discipline, and introduced the main contents, theoretical system, and research methods of the human-water relationship discipline. The practical needs of water control were elaborated from three levels: understanding, analyzing, and regulating human-water relationships, including the needs for ideology-concept, equation-measurement, and model-strategy. Furthermore, the research priorities corresponding to the three levels were given in detail, with a total of 18 specific research directions. This study supports further improving the theoretical system of the human-water relationship discipline and exploring the practical needs and key scientific and technological issues in human-water relationship research.